Application of quality control circle with health education pathway and teach-back method to reduce the incidence of constipation after transurethral resection of the prostate (健康宣教路径联合回授法降低前列腺电切术后便秘发生率的品管圈实践) - NIE Fang (聂芳); CHEN Xiaoxia (陈晓霞); HUANG Guiyan (黄桂燕) (中西医结合护理)
Objective To investigate the application value of quality control circle (QCC)with health education pathway and teach-back method in reducing the incidence of constipation after transurethral resection of the prostate (TURP). Methods A QCC group was set up and theme of QCC activity was to reduce the incidence of constipation after TURP. Influencing factors were analysis based on literature review and cross-sectional study, and key issues and related countermeasures to process improvement were established. The health education pathway and teach-back method were adopted in the QCC, and incidence of constipation before and after implementation of QCC was compared. Results The incidence of constipation dropped from 68. 75%(33/48)before QCC to 18. 75%(9/48)after QCC, with a significant difference(P＜0. 05). Conclusion Based on the education pathway of preventing constipation after TURP, the health education using the teach-back method is effective to reduce the incidence of constipation after TURP and relieve postoperative pain of patients. (目的 探讨健康宣教路径联合回授法在降低前列腺电切术后患者便秘发生率的应用效果。方法 成立品管圈小组, 确定“降低前列腺电切术后患者便秘发生率”主题, 查阅文献并开展现况调查, 分析原因, 确立改善重点, 设定目标值, 制定对策, 构建预防前列腺电切术后便秘宣教路径并采用回授法实施, 对比实施前后前列腺电切术后便秘发生率。结果 前列腺电切术后便秘发生率由实施前的68. 75%(33/48)降低至实施后的18. 75%(9/48), 差异有统计学意义(P＜0. 05)。结论 通过构建预防前列腺电切术后患者便秘宣教路径, 采用回授法进行健康宣教, 能够有效降低前列腺电切术后便秘的发生风险, 减少患者痛苦。)